Postharvest root deterioration or vascular streaking of cassava clones (accessions and breeding lines) was evaluated with harvests at different ages (8 and 12 mo.), seasons (beginning and end of wet season), and locations (CIAT-Palmira, Carimagua, and Caribia in Colombia) to assess the effect of environmental factors on cassava genotypes. Vascular streaking was sensitive to any of these environmental factors. Genotype x location interaction was highly significant suggesting that final cv. selection should be carried out in each location. Genetic analysis carried out in one location suggested that inheritance of vascular streaking was, at least partly, controlled by additive factors and was quantitative rather than qualitative. Narrow sense heritability of 0.64 was obtained. Vascular streaking was highly and significantly correlated with root DM content in all the trials conducted during 7 yr. Since free recombination between resistance to vascular streaking and high root DM content may not be possible, the most acceptable balance between these 2 traits should be defined according to the use of product and edaphoclimatic condition of production area prior to selection program. (AS) - Gabriel, C.J.; Walsh, R.; Nolt, Barry L. (1987)
Several species of double-stranded RNA (dsRNA) were found to occur in the cassava clone Secundina, which was thought to be virus- free. A large dsRNA molecule (6.6 x 106 Mr = relative molecular mass)(L-dsRNA) was shown to be graft, but not mechanically transmitted and occurred primarily in a nuclear-rich fraction isolated from dsRNA-containing Secundina plants. Viruslike particles were not detected in plants containing the L-dsRNA using a var. of purification procedures. L-dsRNA was also found in 2 non- Secundina cassava introductions. Smaller dsRNAs(S-dsRNAs), ranging mainly between 0.61-0.41 x 106 Mr, were also detected in some Secundina plants containing the L-dsRNA. The S-dsRNAs were not transmissible by mechanical inoculation or grafting. All dsRNAs could be eliminated by meristem-tip culture of infected plants. DsRNA analysis is recommended for indexing cassava for this latent viruslike agent. (AS)